Development and Optimization of a Novel Damper Control Strategy Integrating DCV and Duct Static Pressure Setpoint Reset for Energy-Efficient VAV Systems - Pasidu Dharmasena; Nabil Nassif (Buildings)
Climate change and the need to reduce greenhouse gas emissions have made energy efficiency in modern building operations more critical than ever. This study presents an improved damper control strategy for VAV systems, combined with techniques like DCV and duct static pressure adjustments, to optimize fan energy consumption. Using energy simulations and mathematical models, the research evaluates traditional HVAC operating methods against the proposed novel control approach across diverse climates. Findings show that the refined control integrations effectively adjust ventilation air volumes during low occupancy and achieve up to 47% savings in fan energy, cost, and CO2 savings annually. While DCV alone had minimal impact on fan energy, it significantly reduced the amount of outdoor air that required conditioning, thereby lowering cooling and heating demands. This research highlights the importance of integrating an advanced control strategy in building mechanical systems to reduce operational costs and environmental impact, contributing to sustainability and carbon reduction goals.